2011
DOI: 10.1016/j.bjmsu.2011.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Contrast Enhanced Ultrasound for Investigation of Complex Cystic Renal Masses

Abstract: Objective: Cystic renal masses are conventionally assessed by contrast CT and/or simple ultrasound scan. Contrast Enhanced Ultrasound (CEUS) is a relatively new investigation which may act as a novel tool for investigation of these masses and the aim of this study was to evaluate this potential. Patients and methods: 19 patients underwent CEUS in our Trust for investigation of complex cystic renal masses. The results were compared with other investigation modalities i.e. CT and simple ultrasound scans. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…The Bosniak classification was initially developed solely on the basis of CT findings (14). Subsequently, a few studies have suggested that MRI (7,8) and CEUS (916) may be equally useful for characterization of complex renal cystic masses. These studies are predominantly based on retrospective series.…”
Section: Discussionmentioning
confidence: 99%
“…The Bosniak classification was initially developed solely on the basis of CT findings (14). Subsequently, a few studies have suggested that MRI (7,8) and CEUS (916) may be equally useful for characterization of complex renal cystic masses. These studies are predominantly based on retrospective series.…”
Section: Discussionmentioning
confidence: 99%
“…Shahzad et al studied several renal lesions of which two were eventually diagnosed as cystic nephroma on histology 3 . They found both had ‘malignant enhancement’ on contrast ultrasound but did not describe quantitatively and it is uncertain if time intensity curves are similar to our case.…”
Section: Discussionmentioning
confidence: 56%
“…BC new applies to contrast-enhanced CT and MRI. Although the role of ultrasound is not fully established, CEUS can be potentially useful in the evaluation of complex cystic renal lesions [16,17]. Moreover, CEUS is particularly attractive due to its lower cost, lack of ionizing radiation and non-nephrotoxic microbubble contrast agents.…”
Section: Discussionmentioning
confidence: 99%